Enhanced Crop Productivity and Sustainability by Using Native Phosphate Solubilizing Rhizobacteria in the Agriculture of Arid Zones - Maldonado, Stefanie; Rodríguez, Andrés; Ávila, Bastián; Morales, Paloma; González, Máximo Patricio; Araya Angel, Juan Pablo Andres; Olalde, Victor; Bravo, Jaime; Jana, Constanza; Sierra, Carlos; Stoll, Alexandra (Frontiers in Sustainable Food Systems, 2020)
The importance of phosphate solubilizing rhizobacteria (PSB) has been well document as an option for enhancing sustainable agriculture. As a particular group of plant growth-promoting rhizobacteria (PGPR), PSB play an important role in the soil phosphorus cycle, increasing the bioavailability for growth and plant development. This study analyses the plant growth-promoting effects of 5 strains (BN0009, BN0013, BN0015, BN0024, and BN0035) out of 180 isolated from Jarava frigida (Phil.) F.Rojas (Poaceae), a native grass from the Andean Atacama desert from North of Chile. The five bacterial isolated (BN strains) were identified as non-pathogenic Erwinia sp. and show a high phosphate solubilization capacity for Ca(PO4) ranging from 608.9 to 781.4mg/L. Strains IAA production varies between with 23.5 and 35.9mg/L, siderophores, phosphatase (alkaline and acid) production was also observed, but none of the five isolated presented antagonism responses against plant pathogens Botrytis sp. and Sclerotinia sp. All isolates enhanced seed germination in Lactuca sativa and Solanum lycopersicum (excepting BN009). Additionally, all strains stimulated the early root elongation and seedling development in lettuce and tomato. Pot experiments displayed that BN0015, BN0024, and BN0035 significantly promote plant growth regarding root and leaf area, root and leaf weight, as well as leaf number compared with non-treated plants. In a field experiment with lettuce and two fertilization treatments (50% and 100% of the recommended crop fertilization), the BN0024 application improved crop productivity compared to the respective control. P content in plants with bacterial inoculations increased significantly compared to control in either fertilization treatment, suggesting an improved nutrient uptake. Also, lettuce with 50% fertilization and inoculation with BN0024 equate productivity with the control 100% fertilization. Finally, we discuss these results in the context of applicability to enhance the agroecosystem productivity in arid and semiarid zones.